IMPLIKASI KEPUTUSAN INVESTASI TERHADAP NILAI PERUSAHAAN SEKTOR REAL ESTATE AND PROPERTY DI BURSA EFEK INDONESIA: FAKTOR RISIKO DAN RASIO LIKUIDITAS SEBAGAI VARIABEL INTERVENING - YULIANI . (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2013)
The study aims to describe and analyze the investment decision direct effect on firm value, to measure and analyze risk factors as intervening variables effect the investment decisions on firm value, and measure and analyze the liquidity ratio as an intervening variable effect investment decisions on firm value. The research was conducted in the real estate and property sector in Indonesia Stock Exchange (IDX) with the observation period 2007-2011. The sampling method is saturated. The unit of analysis as many as 85 cases by using Structural Equation Modeling (SEM) based on variance, using SmartPLS Ver 2.0 M3. Research findings that investment decisions significant and positive direct effect on firm value. Risk factors as partial mediation with a negative coefficient as the effect of investment decisions on firm value. Liquidity ratios and significant role as a negative influence investment decisions on firm value with the variable role is partial mediation.